2012
DOI: 10.1186/1471-2164-13-381
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plant-derived miRNAs in animal small RNA datasets

Abstract: BackgroundPlants contain significant quantities of small RNAs (sRNAs) derived from various sRNA biogenesis pathways. Many of these sRNAs play regulatory roles in plants. Previous analysis revealed that numerous sRNAs in corn, rice and soybean seeds have high sequence similarity to animal genes. However, exogenous RNA is considered to be unstable within the gastrointestinal tract of many animals, thus limiting potential for any adverse effects from consumption of dietary RNA. A recent paper reported that putati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
143
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 14 publications
2
143
0
1
Order By: Relevance
“…Here, we observed transfer to occur far below the theoretical optimum, which is in line with other studies examining insects. 21 Such a limiting factor may be overcome by a number of scenarios. Evidence in multiple systems, including the honey bee, suggests that selective transport and amplification of small RNA exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we observed transfer to occur far below the theoretical optimum, which is in line with other studies examining insects. 21 Such a limiting factor may be overcome by a number of scenarios. Evidence in multiple systems, including the honey bee, suggests that selective transport and amplification of small RNA exists.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The first description of such a phenomenon, in the report by C-Y Zhang and colleagues, 18 showed that dietary plant miRNAs could enter the mammalian bloodstream and regulate cholesterol metabolism in the ingesting animal. This study stimulated much interest and further investigation [21][22][23][24] since its initial publication. Since then, however, multiple groups have been unable to reproduce these findings.…”
Section: Introductionmentioning
confidence: 99%
“…87 First, the biological relevance was argued, suggesting that the presence of the exogenous miR168a was just an artifact as a result of sequencing methods. 88 On the other hand, the available data are controversial on the efficiency of gastrointestinal absorption for xeno-miRNAs. While the animal-derived miRNAs might be absorbed in significant quantity and might have biological relevance, 63 the amount of absorbed plant-derived miRNAs did not reach meaningful quantity in some investigations.…”
Section: Dietary Xeno-mirna Acting In a Cross-kingdom Fashionmentioning
confidence: 99%
“…36 In a different study, Zhang et al found no evidence of miRNAs in a number of invertebrates including pea aphid and silkworm and no uptake of miRNAs in feeding experiments with the corn rootworm. 29 By contrast, analysis of uptake of other sRNA types in corn rootworm fed on wild-type plants by another group revealed uptake of plant endogenous long dsRNAs, but not small sRNAs, 37 with no apparent effect on the transcriptome. This same group found uptake in another coleopteran species, the Colorado potato beetle, but no uptake was observed in 2 lepidopteran species.…”
Section: Introductionmentioning
confidence: 97%
“…25 These studies stimulated much interest, 26,27 and in conjunction with studies showing other sources of exogenous sRNA, 28 particular emphasis was placed on the paradigm-shifting possibility of cross-kingdom communication mediated through the diet. However, a number of subsequent studies provided considerable evidence that systemic uptake of orally ingested foreign miRNAs, as a class of molecules, is negligible in mammals [29][30][31][32] and significantly below levels required to be biologically relevant when acting through canonical sequence-specific RNAimediated mechanisms. With respect to dietary uptake of miRNA or other sRNA in vertebrates, controversy remains, with a number of groups providing data in support or in opposition (reviewed in 33,34 ).…”
Section: Introductionmentioning
confidence: 99%